HUBUNGAN POLA ASUH ORANG TUA OTORITER TERHADAP MOTIVASI BELAJAR MATEMATIKA KELAS III - Nuraheti, Suci; Maksum, Arifin; Nurhasanah, Nina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The development of many children was more likely to play handphone than to study. This makes the child lose his motivation to study. Children's learning motivation can be influenced by various factors, one of which is parenting. Parents who have a good parenting will have an impact on children's learning motivation. This study aims to examine the relationship between authoritarian parenting and mathematics learning motivation of elementary school 3rd graders by examining the difference between male and female students learning motivation in class mathematics. The type of research used in this study is the study of correlation with a robustitative approach. Sampling techniques using simple random sampling techniques with the subject being students grade III at Kebon Jeruk 08 Elementary School number as many as 30 students. Data collection techniques are using instruments in the form of quisioner. The data obtained are analyzed using descriptive statistics and inferential statistics. Inferential statistical analyses used include 1) normality tests, 2) linearity tests, 3) hypothesis tests (correlation of pearson product moment). The research results show that the relationship between authoritarian parenting and III grade students' mathematical learning motivation of 0.534 is classified as moderate. Thus, it can be concluded that there is a significant and positive relationship between parenting and motivation for third grade students' math learning.